Daya Terima Permen Jelly Buah Pedada (Sonneratia Caseolaris) dengan Penambahan Karagenan - Dwi Tria Ramadani; Dini Wulan Dari; Aisah Aisah (Jurnal Akademika Baiturrahim Jambi, 2020)
Pedada fruit (Sonneratia caseolaris) is one of the mangrove varieties that has a high nutritional content and has the potential as an antioxidant. In general, pedada is still underutilized by the community because it tastes sour and feels tight when consumed directly. One of the efforts in utilizing the pedada fruit is processing it into jelly candy. The purpose of this study was to determine the acceptability (color, flavour, texture and taste) of pedada jelly candy with the addition of carrageenan. This research is an experimental design. This study was used a completely randomized design (CRD) of 2 factors: carrageenan (10 grams and 20 grams) and the addition of pedada juice extract (control, 50 ml, 100 ml) obtained 6 combinations. To find out the acceptability, the organoleptic test using the hedonic method using 30 panelists were rather trained. This research was conducted in May-August 2018. Jelly candy making and organoleptic test was carried out at the STIKes Baiturrahim Jambi Nutrition and Food Laboratory. The best treatment in making Pedada jelly candy which is very preferred, namely P2K2 (100 ml pedada fruit juice and 20 gr carrageenan) with a color score of 5.87, taste 4.74, flavour 4.74, texture 5.28 .